Lithium-ion battery with stable silicon-ionic liquid interface

By using a nano-silicon-room temperature ionic liquid system in lithium-ion batteries, a stable and elastic solid electrolyte intermediate layer is formed, and a battery instability caused by volume expansion of silicon material is solved, and a lithium-ion battery with high energy density and long life is achieved.

JP2025038208AInactive Publication Date: 2025-03-18THE REGENTS OF THE UNIVERSITY OF COLORADO
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024226072
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2014-10-30
Filing Date
2024-12-23
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The volume expansion of silicon material in lithium-ion batteries during charging and discharging leads to instability of the solid electrolyte intermediate layer, resulting in shortening of battery life and damage to conductivity paths.

Method used

Using a nano-silicon-room temperature ionic liquid (RTIL) system, a very stable and elastic solid electrolyte intermediate layer is formed by using RTIL electrolytes such as PYR13FSI and EMIMFSI in nano-cyclized polyacrylonitrile (cPAN) electronetodes.

Benefits of technology

Long-term and stable operation of nano-silicon lithium-ion batteries is achieved, which significantly improves the cycle life and energy density of the battery, while reducing the cost of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038208000001_ABST
    Figure 2025038208000001_ABST
Patent Text Reader

Abstract

To provide a battery capable of achieving high energy density and long cycle life at low cost.SOLUTION: A lithium ion battery includes an electrode system including an active material including a plurality of nanosilicon and a polyacrylonitrile polymer that binds the active material and conducts electricity and lithium ions, a second electrode, and a room temperature ionic liquid electrolyte for contacting the electrode system and the second electrode.SELECTED DRAWING: Figure 17
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Application No. 62 / 072,957, filed October 30, 2014, the entire contents of which are incorporated herein by reference.

[0002] This invention was made with Government support under Grant No. IIP1152040 awarded by the National Science Foundation. The Government has certain rights in this invention.

[0003] The present disclosure relates to energy storage devices. More particularly, the present disclosure describes lithium ion batteries. [Background technology]

[0004] The volume expansion of silicon during lithiation is problematic for use as a battery material. Commercially available graphite electrodes expand by about 10-13% during lithium intercalation, while silicon expansion can reach nearly 300%, resulting in structural degradation and instability of the solid electrolyte interphase. Such instability ultimately shortens the battery life to an unsatisfactory level, causing destruction of the conductive pathways, separation of active materials, modification of the continuous solid electrolyte interphase, and a mechanically unstable solid electrolyte interface.

[0005] A solid electrolyte interlayer is formed on the anode surface by reductive decomposition of the electrolyte during charging of the battery. Silicon anodes suffer from the lack of a dynamic solid electrolyte interlayer, which must be reformed with every cycle, as expansion during lithiation causes the layer to break down. The formation of the solid electrolyte interlayer occurs when Li + consumes electrolyte with each cycle. + In contrast to half cells that utilize a Li metal counter electrode with a supply of Li, full cells utilize a Li metal counter electrode provided by the cathode. + The continuous destruction and modification of the solid electrolyte interlayer will rapidly destroy the cycling performance of the battery.

[0006] Alternative electrolyte compositions and surface treatments of active materials have been investigated to enhance SEI formation on high capacity anode materials and improve the CE of half-cells. Despite these efforts, the CE achieved throughout cycling is still insufficient for long-lasting Si-based full cells, or the methods used to fabricate the full cells introduce a large excess of Li into the system that disguise its true performance. + In an effort to design next-generation electrolyte materials, room-temperature ionic liquids (RTILs or ILs) are of interest due to their low volatility, negligible vapor pressure, high thermal stability, high voltage stability, and sufficient ionic conductivity. RTILs, especially pyrrolidinium (PYR1 n+ ) or 1-ethyl-3-methyl-imidazolium (EMIM + ) cation and bis(trifluoromethanesulfonyl)imide (TFSI - ) or bis(fluorosulfonyl)imide (FSI - ) anions are cathodically stable with common anode materials containing Si. A clear understanding of the electrochemical properties and interfacial chemistry of these materials is yet to be developed. Little work has been done on the compatibility of RTIL electrolytes with Si-based nanocomposite electrodes, and Si-RTIL systems with thin-film electrodes have been investigated.

[0007] For these and other reasons, there is a need for battery materials that can provide high energy density and long cycle life at low cost. [Brief description of the drawings]

[0008] [Figure 1A] The capacity and coulombic efficiency of the nSi-cPAN electrode in PYR13FSI (1.2M LiFSI) and EC / DEC (1M LiPF6) are shown. [Figure 1B] Figure 1 shows the capacity and coulombic efficiency of nSi-cPAN electrodes in PYR13FSI (0.6 M LiTFSI) and EMIMFSI (1.2 M LiFSI) electrolyte systems. [Figure 2A-2H]A diagram of the decomposition mechanism on the Li13Si4 surface is shown. [Figure 3A-3G] 1 shows a microscopic image of the solid electrolyte intermediate composition in the Si-PYR13FSI system. [Figure 4A-4B] The mass change of the nSi-cPAN electrode during the first charge-discharge cycle is shown. [Figure 5A-5H] 1 shows a microstructure image of the anode. [Figure 6A] The charge capacity and coulombic efficiency of nSi-PAN / L333 full cells assembled with PYR13FSI (1.2M LiFSI) and conventional EC / DEC (1M LiPF6) electrolytes are shown. [Figure 6B] The results of full cell ratio testing and long-term cycling of nSi-cPAN / PYR13FSI / L333 are shown. [Figure 6C] A mock-up of a commercial 18650 cell is shown demonstrating the opportunity to incorporate more electroactive material due to the relatively thin nSi-cPAN electrodes. [Figure 7A] Voltage profile of EC / DEC (1M LiPF6) using nSi-cPAN is shown. [Figure 7B] The voltage profile of PYR13FSI (1.2M LiFSI) using nSi-cPAN is shown. [Figure 7C] The voltage profile of PYR13FSI (0.6M LiTFSI) using nSi-cPAN is shown. [Figure 7D] The voltage profile of an EMIMFSI (1.2M LiFSI) using nSi-cPAN is shown. [Figure 8A-8D] The single-electron reduction of the anions of FSI- and TFSI- is shown. [Figure 9A-9E] 1 shows cross-sectional images of the solid electrolyte intermediate composition of cycled conventional Si-based electrodes. [Figure 10A-10B] The figure shows the mass change per electron for each electrode during the first charge-discharge cycle. [Figure 11] 1 shows the electrochemical performance of a half-cell of a conventional Si-based electrode with PYR13FSI for an EC / DEC electrolyte system. [Figure 12] The high temperature electrochemical performance of the full cell is shown. [Figure 13A] The capacity and coulombic efficiency of the electrodes are shown. [Figure 13B] The capacity and coulombic efficiency of the full cell are shown. [Figure 14] 1 illustrates a composition comprising a film formed on an electrode having a film comprising fluorine, oxygen, sulfur, carbon, and lithium. [Figure 15] FIG. 1 shows a diagram illustrating a substrate containing active material including nanosilicon, a polymer that binds the active material and conducts electricity, and an electrolyte that provides contact between the polymer and the active material. [Figure 16] The present invention shows a substrate including active materials including nanosilicon, polyacrylonitrile for binding the active materials and conducting electricity, and an electrolyte in contact with the active materials, the electrolyte including a LiFSI salt and an anion of the bis(fluorosulfonyl)imide (FSI-) of the LiFSI salt. [Figure 17] FIG. 1 shows a block diagram of a device including a first electrode comprising nanosilicon, a second electrode, and a room temperature ionic liquid electrolyte in contact with the first electrode and the second electrode. [Figure 18] FIG. 1 shows a flow diagram illustrating a method that includes charging and discharging a battery containing an electrolyte and forming a solid electrolyte interlayer containing fluorine, oxygen, sulfur, carbon, and lithium on an electrode. [Figure 19] FIG. 1 shows a flow diagram of a method including charging and discharging a battery having an electrode comprising nanosilicon coated with polyacrylonitrile, forming a solid electrolyte intermediate film comprising fluorine, oxygen, sulfur, carbon and lithium on the electrode, and covering the conformally coated polyacrylonitrile with fluorine, oxygen and sulfur. [Figure 20] 1 shows a flow diagram of a method that includes charging and discharging a cell having electrodes that include nanosilicon and forming a substantially mechanically stable solid electrolyte interface on the electrodes. [Figure 21]FIG. 1 shows a block diagram of a system including a plurality of electrically coupled cells including a first electrode including nanosilicon, a second electrode, and a room temperature ionic liquid electrolyte in contact with the first electrode and the second electrode.

[0009] A combinatorial approach involving a mechanically resilient electrode structure merged with an electrolyte capable of forming a good SEI is one option to integrate structural integrity with stable interfacial chemistry in bulk-type Si anodes. To this end, we designed a nano-Si-RTIL system that exhibits a highly stable and resilient SEI, resolving the shortcomings of Si anodes and enabling long-term operation of Li-ion full cells with bulk-type nano-Si-based anodes. A "nano-Si-based electrode" is an electrode that contains silicon active material with a particle size / diameter in the nanometer scale (1-500 nm). We have demonstrated, by a systematic and comprehensive experimental matrix, that the previously reported cyclized polyacrylonitrile (cPAN)-based Si nanocomposite structure (nSi-cPAN) can be used to fabricate FSI. - We have investigated the composition and structure of the SEI formed by the PYR-based IL. Using experimental and theoretical data, we propose a mechanism for the formation of the SEI at the nano-Si-RTIL interface and discuss the importance of the CE in the construction of the half-cell. In particular, this work focuses on the formation of the SEI at the nano-Si-RTIL interface. 13 nSi-cPAN / Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 ) This is highlighted by the groundbreaking demonstration of highly reversible full-cell cycling of O2-(L333).

[0010] The simple fabrication, scalability, low capacity expansion, and structural robustness of the nSi-cPAN architecture make it an ideal candidate for merging with a suitable electrolyte system. To pursue a stable Si-electrolyte interface, the nSi-cPAN composite was cycled under galvanostatic conditions in RTILs consisting of cation-anion combinations known for their cathodic stability against various anode materials. PYR 13FSI (1.2M LiFSI), PYR 13 The cycling performance of the nano-Si-based electrode in RTIL solutions containing TFSI (0.6 M LiTFSI) and EMIMFSI (1.2 M LiFSI) was directly compared to the performance of the electrode in a commercial EC / DEC (1 M LiPF6) electrolyte. The results of the preliminary cycling studies are shown in Figures 1(A) and 1(B), and FSI - Strong and unexpected cycling stability and PYR of nSi-cPAN anode in IL 13 This demonstrates an unexpected CE in the FSI system. Cycling was performed at 0.05-1 V (vs. Li / Li + The results were performed at room temperature on a 2032 coin cell operating between 0.1 and 1.0 V. 13 The high CE exhibited in FSI (1.2 M LiFSI) electrolyte stabilizes after 8 cycles with an average stable CE of 99.945% and charge capacity retention of 76.7% after 100 cycles (Figure 1(B)). While showing stable half-cell cycling, the lower average CE (98.451%) observed with EMIMFSI (1.2 M LiFSI) electrolyte (Figure 1(B)) is consistent with the EMIM below 1.5 V. + Cation instability (Li / Li + These data are in contrast to the cycling behavior of our nSi-cPAN electrodes in conventional organic electrolytes, which maintains only 45.2% of the initial charge capacity after 100 cycles, due to the average stable CE of 97.824% (Figure 1(A)) shown in Figure 7.

[0011] Nano-Si-PYR 13 The unexpected CE of the FSI system can be attributed to the formation of a highly stable SEI. We suggest that the decomposition of ions present in the electrolyte solution leads to a SEI composition that varies depending on the ionization makeup of the RTIL. - We hypothesize that the interface formed by the decomposition products of the IL mitigates the continuous SEI formation experienced in organic electrolytes, and this proposal supports the nano-Si-PYR 13This is evidenced by the longer cycle life of the FSI half-cell (Figure 1(A)), which achieves an average CE of 99.97% at 200 cycles. - Considering the obvious incompatibility with the electrolyte, TFSI - and FSI - The degradation mechanism and SEI composition arising from the IL consisting of were investigated using density functional theory (DFT) electronic structure methods.

[0012] Figure 2 shows the Li 13 The decomposition mechanism of FSI-- and TFSI--based ILs on the surface ball-and-stick model of Si4 is shown. A is FSI - and B is the anion of the decomposed FSI. - where C is the radical dianion of TFSI. - and D is the anion of decomposed TFSI - The dianion of the DFT simulation is Li 13 Intact PYR on Si4 + / FSI - and F is Li 13 Decomposed PYR on Si4 + / FSI - and G is Li 13 Intact PYR on Si4 + / TFSI - and H is Li 13 Decomposed PYR on Si4 + / TFSI - In EH, FSI is a pair. - or TFSI - The excess electrons above are not explicitly added, but are added to Li 13 The Li, Si, C, O, N, S, and F atoms are depicted as silver, green, gray, red, blue, yellow, and purple spheres, respectively. 13 + The cations are shown as grey lines in the background. All panels are optimized geometries except for F and H, which are AIMD snapshots at T=350K.

[0013] Through parallel modeling procedures in two different environments, we are able to compare potential SEI formation pathways in ILs containing both anions. The first type of theoretical study focuses on the formation of isolated FSIs. - (Figure 2(A)) and TFSI - (Fig. 2(C)) to mimic the one-electron reduction pathway in bulk liquid electrolytes. 13 PYR on the (010) surface of a Si4 slab + / FSI - and P.Y.R. + / TFSI - The first modeling study consists of periodic boundary condition simulations of ion pairs at Li. As both modeling treatments give similar results, we will focus the following analysis on the study of ion pairs at the lithiated silicon surface. A detailed description of the localized basis calculations (first modeling study) is provided below and shown in Figure 8. To model the electrolyte molecules in direct contact with the initial anode surface, we first 13 PYR on Si4 surface + / FSI - and P.Y.R. + / TFSI - The ion pairing of is optimized (shown in Figures 2(E) and 2(G) respectively).

[0014] The same model of surface has been previously studied in the context of fluoroethylene carbonate (FEC) decomposition, representing a low-potential anode surface with Si directly exposed to the liquid electrolyte, serving as an electron source that can readily reduce electrolyte molecules in its vicinity.

[0015] After geometric optimization that did not lead to any chemical reaction, ab initio molecular dynamics (AIMD) simulations were started at 350 K. FSI - The anion of F rapidly decomposes within 1.2 ps (Fig. 2(F)). As shown in Fig. 2(B), the SF bond is broken first to give F. -This rapid reaction cascade corresponds to the predicted FSI on the Li metal surface. - Reminiscent of the reaction. TFSI - FSI - It has been shown to be much less reactive than Li 13 When left on the Si4 surface for 21 ps, it decomposes (Figure 2(D)). Neither of the two resulting fragments has a net magnetic moment, and a two-electron reduction occurs, leaving SO2CF3 on the electrode surface. - and NSO2CF3 2- (Figure 2(H)) 13 + remains inactive throughout all of the above simulations.

[0016] To summarize our modeling study, FSI - and TFSI - It can be seen that FSI undergoes a completely different decomposition mechanism during electrochemical reduction. - F - Rapidly releases LiF, most likely to form LiF in the SEI, but not in the TFSI. - forms different products on a much slower time scale. Some of the latter reduced fragments eventually form F - However, the slow PF6 produced by organic electrolytes - As with the decomposition of - Emission is TFSI - We can use F - Fast release of nano-Si-PYR 13 We speculate that this may correlate with the high cycling performance exhibited by the FSI system. This evidence is based on empirical data showing good Si half-cell cycling behavior when FEC is used as an electrolyte additive in organic carbonate-based electrolytes. - This is consistent with previous modeling studies of FEC decomposition showing that it rapidly releases LiF to form LiF.

[0017] By using electron energy loss spectroscopy (EELS) to probe the elemental composition of the surface of nSi-cPAN particles during cycling (16th delithiation), we confirm the DFT predictions and gain insight into the elemental composition of the proposed SEI. Figure 3 shows high-resolution transmission electron microscopy (HRTEM) images in a cross-section (Figure 3(A)) of cycled / delithiated nSi-cPAN with EELS mapping of silicon (Figure 3(B)), carbon (Figure 3(C)), sulfur (Figure 3(D)), fluorine (Figure 3(E)), lithium (Figure 3(F)), and oxygen (Figure 3(G)), defining the elemental composition and preferred nucleation sites of the SEI formed. The clear silhouette of F coating the surface of the Si particles, in combination with the presence of Li, validates the LiF-based SEI seen in our DFT simulations. Furthermore, the clear mapping of O and evidence of S for coating the cPAN surface confirms the previously determined FSI, e.g., LiOH and SO2. - Similar analysis of conventional Si-based electrodes cycled in conventional organic electrolytes shows no specific deposition of electrolyte decomposition products around the cycled Si particles (Figure 9).

[0018] To investigate the proposed mechanism of formation of the SEI on the nSi-cPAN electrode, we investigate the mass change at this interface during the first charge-discharge cycle using an electrochemical quartz crystal microbalance (EQCM). By monitoring the mass gain and loss on the electrode in real time during the first cycle where the SEI forms the substructure, we further demonstrate the mechanical resilience of the nano-Si-RTIL interface while recognizing the fragility of this interface in conventional organic electrolyte-based systems.

[0019] Figure 4 shows the mass evolution of the nSi-cPAN electrode during the first charge-discharge cycle. The EQCM mass maps obtained during the initial SEI formation cycle of the nSi-cPAN electrode cycled with a conventional organic electrolyte (A) and with PYR (B). 13The results are shown for the organic electrolyte (Figure 4(A)) and FSI (1.2M LiFSI) cycled systems, along with the corresponding voltage traces for each system. - We report EQCM mass diagrams for the initial formation cycle of nSi-cPAN in both systems IL (Figure 4(B)). Both systems show two very different behaviors during lithiation, as suggested by modeling studies. Approximately 43 μg cm during the first 20% of lithiation in both systems. -2 The gradual increase in mass corresponds to the uptake of lithium by cPAN, other non-faradaic processes, and the initial alloying of Li with Si.

[0020] The electrodes subsequently undergo rapid mass changes, primarily due to electrolyte decomposition and deposition of decomposition products at the electrode-electrolyte interface. The onset of these rapid mass changes is manifested in the voltage traces of each system via a "potential overshoot" phenomenon, a known artifact of electrolyte decomposition in EQCM experiments. The onset of this rapid mass change occurs earlier (at 20.5% lithiation) and at a significantly higher rate (at 46.1% lithiation) than in conventional organic electrolytes. - 73.1gmol -1 The mass change per mole of electrons (mpe, e - gmol -1 ) was extracted from the data in Figure 10. This is because 13 This is due to the lower electrochemical stability of conventional organic electrolytes compared to FSI systems, and PYR 13 The FSI system has a voltage stability window of 7.31 V. The higher average mpe of the conventional electrolyte system is due to the very slow F during the decomposition of EC / DEC (1M LiPF6). - This suggests the formation of an SEI consisting mainly of decomposed organic molecules, together with the release of PYR 13 Controlled mass gain in FSI (1.2M LiFSI) electrolyte, lower average mpe (at 56% lithiation) - 25gmol -1(reaching high speed F - The release of α-H2O2 confirms the prediction of the formation of an SEI composed of small inorganic molecules such as LiF.

[0021] 282μgcm -2 After reaching a critical mass of , the mass of the Si-conventional organic electrolyte system collapses. The collapse of mass can be caused by many factors, including the severe volume expansion known to occur in this system, which causes the destruction of the electrode matrix, as well as the accumulation and rupture of an unstable interfacial layer. During delithiation, the contraction of the nSi-cPAN composite leads to further breakage and material loss of the electrode matrix. The inability of this system to show a stable mass change corresponds to the incompatibility of Si with the conventional electrolyte. In contrast, the mass diagram of the nano-Si-RTIL system shows a more gradual mass gain and loss after delithiation, with about 73% of the mass obtained during the initial lithiation. We attribute this behavior to the irreversible formation of a stable interfacial layer on the nano-Si electrode, which manifests in stable cycling and high CE throughout the excellent cycle life.

[0022] Although the theoretical and experimental data described provide insight into the proposed formation mechanism and composition of the SEI, we have 13 To directly understand the morphological effects of FSI electrolyte on nano-Si based electrodes, more comprehensive imaging studies will be performed.

[0023] Figure 5 shows the microstructure and PYR of nSi-cPAN on the anode. 13The morphological effect of FSI IL is shown. (A) EELS elemental mapping of carbon and silicon, (B) TEM micrograph of pristine nSi-cPAN electrode shows a thin conformal coating of PAN on the nano-Si particles throughout the non-cycled composite. (C), (D) FESEM images of the electrode cross section before (C) and after (D) initial lithiation showing only 17% electrode volume expansion. E,H TEM micrographs of fully lithiated (E,F) and 16th delithiated (G,H) nSi-cPAN electrodes showing no mechanical defects or significant morphological changes.

[0024] Furthermore, we note that EELS and TEM show a thin, conformal coating of PAN on the nano-Si particles throughout the uncycled composite (Figures 5(A) and 5(B)). The mechanical advantage of the cPAN coating is verified by analyzing the electrode cross-sections at different stages of cycle life, finding an overall volume expansion of only 40% after full initial lithiation with EC / DEC (1M LiPF6) electrolyte. 13 By identical processing of electrode cross-section samples taken before (Figure 5(C)) and after (Figure 5(D)) the initial lithiation in FSI (1.2 M LiFSI) electrolyte, we find a volume expansion of the nSi-cPAN composite to be only 17%. To further investigate this unexpected volume control, TEM micrographs were taken after the initial lithiation (Figures 5(E) and 5(F)) and the 16th delithiation (Figures 5(G) and 5(H)). TEM images of both the fully lithiated and cycled electrodes show no mechanical defects or morphological changes within the Si particles or the composite structure. Most notably, the Si-PYR 13 The FSI system shows no severing of the connection between the Si particles and the cPAN network after the 16th delithiation, along with remarkable preservation of the spherical shape of the nano-Si, which contrasts with the relatively poor preservation of the nanostructure of the same electrode in conventional electrolytes. 13The impressive structural integrity of the FSI system is undoubtedly related to the cycling stability of the system, suggesting that the nano-Si-RTIL interface simultaneously promotes good electrochemical and structural resilience.

[0025] As mentioned previously, the goal of much electrochemical research is to incorporate high capacity electrodes into a full lithium-ion cell. To this point in our research, we have focused on nano-Si-PYR 13 We present a detailed evaluation of the FSI system and propose a mechanism for the system's stability via an unexpectedly strong SEI. The most reliable means of substantiating the claim for a stable SEI is the nano-Si-PYR. 13 The objective of this study is to demonstrate long-term cycling of full cells incorporating the FSI system. To this end, we have developed a nSi-cPAN / PYR 13 An FSI (1.2 M LiFSI) / L333 LIB was constructed (see below for details of full-cell fabrication).

[0026] FIG. 6(A) shows the results of conventional EC / DEC (1M LiPF6) and PYR 13 We compare the performance of a nSi-cPAN / L333 full cell assembled with FSI (12M LiFSI) electrolyte. Both cells shown in Figure 2 and Figure 6(A) contain the same electrode mass loading (within 10%) on both the cathode and anode and are operated under the same parameters for a fair comparison. 143.21 mAhg -1 and 127.10mAhg -1 The initial charge capacities (all full cell specific capacities are normalized to the total active material mass) of EC / DEC (1M LiPF6) and PYR 13The maximum capacity of the PYR LIB is 1.2 M LiFSI, and 1.5 M LiFSI. The maximum capacity of the PYR LIB is 1.2 ... 13 Cells cycled in FSI (1.2M LiFSI) electrolyte showed unexpected stability with an average irreversible charge loss of 0.076% over the first 100 cycles with negligible Li consumption, yielding 110.98 mAhg at a rate of C / 2. -1 Nano-Si-PYR provides an average charge capacity of 13 To further investigate the SEI stability of the FSI system, the full cells were cycled over their lifetime in short rate tests. Figure 6(B) shows that the SEI yields of 107.33, 74.70, and 58.26 mAhg at rates of 1C, 4C, and 6C, respectively. -1 Send 1000 cycles of nSi-cPAN / PYR 13 Shows battery operation of FSI (1.2M LiFSI) / L333.

[0027] PYR 13 FSI RTILs enhance the performance of a range of previously developed Si-based anode structures, as well as those containing PAN (Figure 11). Furthermore, preliminary studies of the high-temperature performance of nano-Si-RTIL systems have also yielded promising results (Figure 12), with PYR 13 This suggests that the SEI formed by FSI is stable even at high temperatures. It is understood that the overall energy density of LIBs is limited by the capacity of the positive electrode. This work shows the progress of research on LIB anode materials. As shown in Figure 6(c), the application of nano-Si-PYR to a commercial 18650 cell configuration was 13 We show that the introduction of the FSI system allows for the incorporation of more electroactive materials due to the relatively thin nSi-cPAN electrodes. -2Based on commercial batteries with areal capacity of 10000V, utilizing nSi-cPAN electrodes, which are less than one-quarter the thickness of conventional graphite electrodes, would permit LIBs with much higher energy density. When validated by cycling data and a combination of theoretical and experimental results, our approach to developing a stable, high-energy density anode-electrolyte system represents a significant advancement toward safer, higher-performance secondary LIBs.

[0028] (Methods - Preparation of electrodes and electrolyte) nSi-cPAN and Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2 electrodes were fabricated according to our procedure. The mass loading of active material in both the cathode and anode is at least twice that of previous studies. The ionic liquid electrolyte was provided by Boulder Ionics Corporation (USA) and was scanned for halide impurities. The impurities (F - , C.I. - , Br - , SO4 - ) was quantified using a Dionex ICS-1100 chromatograph, calibrated with a low sensitivity of 1 ppm. Ion chromatography was performed for all ionic liquids and lithium salts used in this study, and the total impurity content of each solution was calculated based on the mass percentage of the electrolyte components in the total mass of the electrolyte. The solutions contained less than 20 ppm (w / w) water and less than 10 ppm (w / w) halide and metal ion impurities. 1 M LiPF6 in ethylene carbonate:diethyl carbonate (50:50, Soulbrain) was used as the conventional organic electrolyte.

[0029] (Electrochemical properties) Electrochemical measurements were performed using an Arbin™ BT2000 battery test station. All half-cells were assembled using the prepared nSi-cPAN electrode as the working electrode and lithium metal foil as the counter electrode. The separator was a glass microfiber disk (Whatman™ GF / F) and the shell was a stainless steel CR2032 coin cell (Pred Materials). The electrolyte system used was EC / DEC (1M LiPF6), PYR 13 FSI (1.2M LiFSI), PYR 13 The half-cells were: TFSI (0.6M LiTFSI), and EMIMFSI (1.2M LiFSI). We used a constant current (CC) test scheme to cycle the half-cells. No retention was utilized during cycling to reveal the true performance of the cell's coulombic efficiency. The half-cells were cycled at 0.05 and 1 V (vs. Li / Li + ) at various cycle currents (C / 10 ratio is 353.6 μA / cm -2 The half-cells were discharged (lithiated) and charged (delithiated) at 2 and 4.15 V (vs. Li / Li). The electrochemical measurements of the half-cells were all normalized based on the mass of Si active material in each electrode (typically 1.1-1.3 mg). We used a constant current constant voltage (CCCV) test method to cycle the full cells. The full cells were cycled at 2 and 4.15 V (vs. Li / Li + ) were charged and discharged at various cycling currents (C / 2 ratio is 502.9 μA cm for the full cell in Figure 6(A). -2 and 197.3 μA cm for the full cell in Figure 6(B). -2 The full-cell electrochemical measurements were all averaged over the total mass of electroactive material in both the cathode and anode electrodes (typically 7-9 mg).

[0030] (electronic structure calculation) The two types of calculations were carried out as described above. 13 A detailed description of ab initio molecular dynamics (AIMD) simulations using slabs of S4 is included.

[0031] (morphological characteristics) A FIB (FEI, NOVA200 dual beam system) equipped with a movable airlock chamber was used for TEM sample preparation. TEM and EELS analysis were performed using an FEI Tecnai F20 operated at 200 keV.

[0032] (Electrochemical Quartz Crystal Microbalance) Similar to the electrode preparation for coin cell testing, the nSi-cPAN film was coated onto a 1 inch diameter Pt 5 MHz resonant crystal (Stanford Research Systems; SRS). The electrochemically active area in the cell was estimated to be 1.359 cm based on the Pt pattern on the crystal. 2 It was determined that the frequency of the nSi-cPAN film was 0.1 μm. To mitigate errors associated with frequency measurements using thick films on quartz crystals, all nSi-cPAN films were fabricated with a thickness of less than 10 μm. The crystal was placed in a crystal holder of an SRS QCM200. The holder was modified with PEEK insulation to allow a stand-alone cell of 2.5 mL volume to be enclosed with a lid. The ceiling of the cell was lined with a foil counter electrode of Li and connected to a copper wire. All current and potential parameters were consistent with the electrochemical properties of the coin cells.

[0033] (Full cell preparation) Full cells were made from the preconditioned electrodes, selected on the basis of their deliverable capacity. An nSi-cPAN anode was fabricated and combined with an L333 cathode, with a total anode capacity of about 160% of the cathode capacity, calculated from the mass of active material. Both electrodes were preconditioned: the anode was allowed to run for 10 charge-discharge cycles in a half-cell configuration and the anode was stopped after full lithiation, while the cathode was allowed to run for 3 charge-discharge cycles in a half-cell configuration and stopped after full delithiation. The half-cell was then disassembled and the electrodes were used to make a 2032 coin cell (Al-coated cathode cup) type full cell. This preconditioning method allows full control of the amount of lithium in the system.

[0034] (Modeling Study 1: FSI in Bulk Liquid Electrolyte - and TFSI - (single-electron reduction of Figure 8 shows the FSI - and TFSI - Diagram (A) shows the single-electron reduction of the anion Li + (TFSI - ) 2. Diagram (B) shows that adding an excess electron to (A) increases the resulting FSI - The diagram (C) shows the spontaneous decomposition of the radical dianion of Li + (TFSI - )2. Diagram (D) shows that adding an electron to (C) results in the resulting TFSI - The first type of theoretical study shows that the isolated FSI - (Figure 8(A)) and TFSI - (Figure 8(B)) anion, Li + The results consist of localized foundational calculations of cluster systems on anions coordinated to Li and "solvated" in a dielectric continuum that approximates the effect of the ionic liquid around them. These mimic the one-electron reduction pathway in bulk liquid electrolytes, which should occur when the rate of electron transfer is slowed by the formation of an initial SEI. + (TFSI -Adding an extra electron to the cluster of )2 spontaneously leads to the FSI in the geometric optimization calculation. 2- From the radical dianion of F - This results in a loss of Li (Figure 8(C)). + (TFSI - )2 to e - and performing geometric optimization to obtain the TFSI 2- is broken down into two fragments, as shown in Figure 9(d): SO2CF3 - and NSO2CF3 - The latter is a radical anion. - Our predictions for Li + No isolated TFSI - The predictions are similar when the hybrid PBEO functional is used. These calculations are consistent with the calculations performed on the four-coordinate Li + Two FSIs to give - or TFSI - It is used in the case of Li + FSI - Or Li + TFSI - Adding to the cluster of Li + The non-physical reduction of Li 0 Note: The above is a static calculation for a single excess electron system that is unrelated to reaction kinetics or electron transfer rates.

[0035] Figure 9 shows the solid electrolyte intermediate composition of a cycled conventional Si-based electrode. The cross section of the electrode contains active material (Si, 50 nm Alfa Aesar), conductive additive (acetylene black, AB), and binder (polyvinylidene difluoride, PVDF) in a ratio of 60:20:20, respectively, and is cycled at 0.05-1 V (vs. Li / Li) using an electrolyte of EC / DEC (1M LiPF6). +) cycled from 0.1 μm to 100 μm. FIG. 9(A) shows TEM micrographs of a cycled conventional Si-based electrode section that has been delithiated 20 times along with EELS elemental mapping of (B) silicon, (C) phosphorus, (D) fluorine, and (E) lithium, defining the likely elemental composition of the formed SEI and showing no predominant attachment on the Si particles.

[0036] (electronic structure calculation method) Two types of calculations were performed: Li and two FSI - or TFSI - Static cluster system calculations with the anions of were carried out using the Gaussian suite of programs, both PBE and PBE0 functionals, a basis set of 6-31+G(d,p) for optimization, and the dielectric continuum of SMD with the permittivity ε set to approximately 40. One extra electron was added in these calculations so that the clusters exhibited a net charge and net spin of -2|e|.

[0037] Li 13 Ab initio molecular dynamics (AIMD) involving Si4 slabs and anions was carried out using PAW pseudopotentials in the VASP code, version 4.6, and is based on spin-polarized DFT / PBE calculations. The simulation cell dimensions are 2 × 1 × 2 Monkhorst-Pack Brillouin sampling, a 400 eV cutoff for the wavefunction, a 1 fs time step, and 10 -6 The energy convergence standard of 15.84×34.00×13.32 eV was applied to the (010) surface. 3 The protons are of known tritium mass, and the Nose thermostat maintains the simulation temperature at T = 350 K. Therefore, the reported time scales are approximations and cannot be directly compared to measurements. 13 + / FSI - and Pyr 13 + / TFSI - The ion pair of Li 13The potentials ("voltages") involved in such calculations are not estimated transparently, but the decomposition mechanisms are generally invariant over a large potential window.

[0038] Figure 10 shows EQCM mpe data obtained during the initial SEI formation cycle of cycled nSi-cPAN electrodes, along with the corresponding voltage traces for each system, in A, conventional organic electrolyte, and in B, PYR. 13 The electrolyte for FSI (1.2 M LiFSI) is shown. The mpe data are segmented between the onsets of different mass changes (grey dotted lines) and the average of these is plotted within the plot for each system. The initial average mpe values ​​(e - 13gmol -1 ) is a process that is used to synthesize Li from cPAN, other non-Faraday processes, and the initial alloying of Li with Si. + After this initial state, the difference in mpe between the two systems is a function of the ability of each system to lithiate-delithiate the nSi-cPAN electrode and form a stable interfacial layer. Of note, the average of 25 gmol -1 e - mpe, which corresponds to the formation of LiF compounds.

[0039] (Electrochemical Quartz Crystal Microbalance (EQCM): Potential Overshoot and Mass Per Mole of Electron (mpe) Analysis) The above-mentioned "potential overshoot" phenomenon has been observed in previous studies using both organic and IL-based electrolytes in coin cell and flooded cell configurations of EQCM. x The overshoot is generally due to the nucleation of Li2O and other decomposition products as the native oxide on the silicon film, of formula Si, is reduced.

[0040] SiOx +2xLi++2xe - →xLi2O+Si (SI)

[0041] As mentioned in the text, the mpe value can be used to infer that reaction products are adsorbed on the electrode. The following analysis provides a hypothesis for the mechanistic aspects of our EQCM experiments and mpe data. The mpe value is calculated by dividing the mass gain by the charge passed and multiplying by the Faraday constant. The mpe values ​​plotted in Figure 2 are average values ​​taken periodically during the SEI formation stage. For an already oxidized Si surface, reduction by Li resulted in 6.9 gmol -1 e - If oxygen is extracted from the solvent, the total mpe will be 14.9 gmol -1 e - (molecular weight of Li2O divided by 2 moles of electrons). For the organic electrolyte, the overshoot at 20% lithiation, observed as a significant increase in potential in the voltage trace, produces a more rapid spike in mpe until a certain stress in the system produces a sudden drop in mass at about 58% lithiation. The mpe values ​​for the organic inflow and outflow suggest that as the potential becomes more negative, the decomposition pathway shifts from the formation of Li2O to the adsorption and decomposition of ethylene carbonate, and finally the decomposition of phosphorus and fluoride species from LiPF6.

[0042] The potential overshoot that correlates with the formation of Li2O in the RTIL electrolyte, when in fact present at about 0.12 V, was a much smaller overshoot than that observed when the potential reached 0.06 V. At this point, there was also a significant increase in potential, indicating an increase in the slope of the mass increase (i.e., the mpe value). Just prior to the increase, the mpe value was about 9 gmol -1 e - The mpe value then increases toward and stabilizes around 25 gmol, which suggests the nucleation of LiF. This is due to the FSI- This corroborates the EELS measurements as well as computational simulations which suggest that the SF bond is broken first when is decomposed. -1 e - The small drop to 1000 likely indicates a weighted average of LiF as well as lighter products such as LiOH and perhaps more Li20. Finally, towards the end of the SEI formation process, the mpe value drops to 33 gmol -1 e - may be elevated below 0.01, indicating incorporation of S containing degradation fragments. - This doesn't make sense since is thought to be the final decomposition product remaining when reacting with Li.

[0043] Figure 11 shows the PYR for the EC / DEC electrolyte system. 13 The electrochemical performance of a half-cell of a conventional Si-based electrode with FSI is shown. The electrode, consisting of active material (Si, 50 nm Alfa Aesar), conductive additive (acetylene black, AB), and binder (polyvinylidene difluoride, PVDF) in a ratio of 60:20:20, was heat treated at 300 °C (to improve the performance of the PVDF binder) and coated with EC / DEC (1M LiPF6), black profile, and PYR 13 FSI (1.2M LiFSI), 0.05-1V (vs. Li / Li) using an electrolyte with an orange profile + ) cycled. 13 Consistent with the results seen in the FSI system, faster capacity stability was observed with PYR 13 2065.77mAhg at 160 cycles with an average CE of 99.377% for a conventional Si-based electrode acclimated to FSI electrolyte. -1 This is observed with an average stable charge capacity of 1092.19 mAhg along with an average CE of 96.553% for the conventional Si anode acclimated in EC / DEC electrolyte. -1 Compare with the average stable specific capacity of PYR 13The improved performance and high CE achieved with the FSI IL system is attributed to the stable SEI formed, which again shows high capacity retention, suggesting mechanical preservation of the electrode throughout cycling.

[0044] Figure 12 shows the PYR 13 The high temperature electrochemical performance of nSi-cPAN / L333 full cells with FSI RTIL is shown. The specific charge capacity of nSi-PAN / L333 full cells was measured by PYR 13 FSI (1.2M LiFSI) and cycled at 60° C. The cells were preconditioned by cycling for 9 cycles at room temperature (RT) and then at 60° C. This preliminary cycling data shows that PYR 13 This suggests that the SEI formed by FSI is stable even at high temperatures.

[0045] As evidence for the application of this system to other Si active materials, Si nanowires (Ref., SiNWs synthesized by W. Want et al., Applied Surface Chemistry, 2012, 258, 8649) have been carried out. Figures 13(A) and (B) show the PYR 13 We present results for SiNW-cPAN in half-cell and full-cell configurations (cathode of L333) in FSI (1.2 M LiFSI) electrolyte and EC / DEC (LiPF) electrolyte systems.

[0046] FIG. 13(A) shows the PYR 13 Figure 13(B) shows the specific capacitance and coulombic efficiency of the SiNW-cPAN electrode in FSI (1.2 M LiFSI) and EC / DEC (1 M LiPF). 13 The specific charge capacity and coulombic efficiency of nSi-PAN / L333 full cells assembled with FSI (1.2M LiFSI) and conventional EC / DEC (1MLiPF6) electrolytes are shown. 13Full cells assembled with FSI (1.2M LiFSI) have a capacity retention for two cycles of 100% at 200 cycles and 97.5% at 300 cycles.

[0047] FIG. 14 shows an example of a composition 100 including a film 102 formed on an electrode 104, the film 102 including fluorine 106, oxygen 108, sulfur 110, carbon 112, and lithium 114. The film 102 is formed on the electrode 104 during, for example, charging and discharging a lithium ion battery. In some embodiments, the film 102 is a solid electrolyte interlayer. A solid electrolyte interlayer (SEI) film is a film formed on the electrode surface (surface of all exposed particles, including particles within the electrode) during electrochemical cycling. When the electrolyte in contact with the electrode surface decomposes (reductive decomposition), the decomposition products form a solid electrolyte interlayer, which acts to passivate further reactions (reductive decomposition) while allowing further charge transfer. The film 102 is not limited to a particular thickness and may change thickness during charging and discharging a lithium ion battery. The electrode 104 includes a conductive material through which an electric current can flow. An exemplary electrode 104 is an anode including nanosilicon that binds silicon and electrochemically inert polyacrylonitrile. Another exemplary binder is polyvinylidene fluoride (PVDF).

[0048] FIG. 15 shows a diagram of a substrate 200 including an active material 202 including nanosilicon 204, a polymer 206 that bonds the active material 202 and conducts electricity, and an electrolyte 208 in contact with the polymer 206 and the active material 202. The electrolyte 208 includes a salt 210 and an anion of the salt 212. The substrate 200 forms a base on which other materials are deposited or formed. In some embodiments, the substrate 200 is an electrode including the active material 202. The active material 202 includes, in some embodiments, a material that can conduct electricity. The active material 202 is an electrochemically active material. In operation, the active material 202 interacts with ions, such as Li ions, to store a charge. In some embodiments, the active material includes nanosilicon. The active material 202 is not limited to a particular form. In some embodiments, the active material 202 includes a silicon nanowire. In some embodiments, the nanowire has a diameter between about 5 nanometers and about 20 nanometers. In some embodiments, the nanowires have a diameter between about 20 nanometers and about 50 nanometers. In some embodiments, the nanowires have a diameter between about 50 nanometers and about 100 nanometers. Silicon suitable for use in connection with forming the active material 202 is commercially available from Alfa Aesar. In some embodiments, the silicon 204, e.g., silicon particles, are coated in polyacrylonitrile during the electrode fabrication process. Thus, a "PAN coating" covers all of the silicon particles that make up the electrode.

[0049] FIG. 16 shows a substrate 300 including an active material 302 including nanosilicon 304, polyacrylonitrile 306 that bonds and conducts electricity to the active material 302, and an electrolyte 308 in contact with the active material 302, the electrolyte 308 including a salt 310 of LiFSI and an anion 312 of bis(fluorosulfonyl)imide (FSI) of the salt 310 of LiFSI. In some embodiments, polyacrylonitrile is the conductive agent. In addition to the active material and binder, the electrode includes an electronically conductive material intended to enable rapid transport of electrons between the current collector and the active material. After heat treatment, PAN becomes electronically conductive and may be used as both a binder and a conductive agent. Other exemplary conductive agents include acetylene black (AB) and "Super-P" (another type of carbon black) and SFG-6 (graphite).

[0050] FIG. 17 shows a block diagram of a device 400 including nanosilicon 402, a second electrode 404, and a first electrode including a room temperature ionic liquid electrolyte 406 in contact with the first electrode 402 and the second electrode 404. The room temperature ionic liquid electrolyte 406 is not limited to a particular material. The ionic liquid electrolyte is a type of electrolyte material based on room temperature ionic liquids (RTILs). The room temperature ionic liquid electrolyte includes RTILs and salts. The ionic liquid electrolyte 406 is not an organic solvent-based electrolyte. In some embodiments, the room temperature ionic liquid electrolyte 406 includes a species selected from the group consisting of pyrrolidinium, 1-ethyl-1-3-methylimidazolium, bis(trifluoromethanesulfonyl)imide, and bis(fluorosulfonyl)imide. In some embodiments, the room temperature ionic liquid electrolyte 406 includes lithium bis(fluorosulfonyl)imide. In some embodiments, the room temperature ionic liquid electrolyte 406 has 58.4% RTIL by weight based on the molecular weight of the ions. Salt is then added to this RTIL at a concentration of 1.2M (or 1.2 mol / L, 187.09 g / mol of LiFSI salt by weight...224.508 g / L of salt in electrolyte). The first electrode comprising silicon 402 can be formed from a variety of materials. In some embodiments, the first electrode comprising nanosilicon 402 comprises a nanocomposite of cyclized polyacrylonitrile silicon. In some embodiments, the first electrode comprises nSi-cPAN and the electrolyte material, more specifically the room temperature ionic liquid electrolyte 406, is PYR 13The nanosilicon 404-containing electrode 402 has a weight ratio of 30% PAN, 70% silicon by weight. The nanosilicon 402-containing first electrode is not limited to a particular structure or thickness. In some embodiments, the nanosilicon 402-containing first electrode comprises a bulk electrode. The thickness of the bulk electrode exceeds the thickness of the thin film electrode. In some embodiments, the bulk electrode has a thickness 408 between about 10 micrometers and about 50 micrometers. In operation, the device 400 maintains a half-cell coulombic efficiency of greater than about 99.994% over about 5000 cycles in some embodiments that include a bulk electrode. In some embodiments, the nanosilicon 406-containing first electrode comprises a substantially mechanically stable solid electrolyte interlayer. The substantially mechanically stable solid electrolyte interlayer exhibits a substantially constant electrical conductivity over thousands of charge-discharge cycles.

[0051] FIG. 18 shows a flow chart 500 illustrating a method that includes charging and discharging a battery containing an electrolyte (block 502) and forming a solid electrolyte interlayer containing fluorine, oxygen, sulfur, carbon, and lithium on an electrode (block 504).

[0052] 19 shows a flow chart of a method 600 that includes charging and discharging a battery having an electrode including nanosilicon coated with polyacrylonitrile (block 602), forming a solid electrolyte interlayer including fluorine, oxygen, sulfur, carbon, and lithium on the electrode (block 604), and conformally covering the polyacrylonitrile coated nanosilicon with fluorine, oxygen, and sulfur (block 606). For example, in a conformal coating or covering, such as a polyacrylonitrile coating or covering, the polyacrylonitrile coats or covers all active materials, such as nanosilicon or silicon particles, substantially evenly and substantially uniformly to a thickness of about 5 nanometers.

[0053] 20 shows a flow diagram of a method 700 that includes charging and discharging a cell having electrodes including nanosilicon (block 702) and forming a substantially mechanically stable solid electrolyte intermediate in the electrodes (block 704). In some embodiments, charging and discharging the cell including electrodes including nanosilicon includes charging and discharging the cell for at least about 5000 cycles. In some embodiments, the method 700 further includes maintaining a half-cell coulombic efficiency of greater than about 99.994% for at least about 5000 cycles.

[0054] 21 illustrates a block diagram of a system 800 including a plurality of electrically coupled cells 802 including a first electrode 804 including nanosilicon 806, a second electrode 808, and a room temperature ionic liquid electrolyte 810 in contact with the first electrode 804 and the second electrode 808, a membrane 812 formed on the first electrode 804, the membrane 812 including fluorine, oxygen, sulfur, carbon, and lithium, and an electronic device 814 electrically coupled to the plurality of electrically coupled cells 802. The system 800 is not limited to use in connection with a particular electronic device 814. Exemplary electronic devices 814 suitable for use in connection with the system 800 include a processor 816, a motor 818, a turbine 820, a solar cell 822, and a transport device 824. In some embodiments, the transport device 824 includes a truck 826.

[0055] While the apparatus and methods have been described with respect to several embodiments, those skilled in the art will recognize that the apparatus and methods are not limited to the described embodiments, but can be practiced with modification and alteration within the spirit and scope of the appended claims. Thus, the description should be considered illustrative rather than limiting. [Appendix 1] an anode comprising an active material, the active material comprising nanosilicon particles, the nanosilicon particles being coated with cyclized polyacrylonitrile; an ionic liquid electrolyte comprising a room temperature ionic liquid electrolyte and a salt; a film formed on all exposed surfaces of the anode, the film comprising fluorine, oxygen, sulfur, carbon, and lithium; A cathode; 1. An electrical energy storage device comprising: [Appendix 2] 2. The device of claim 1, wherein the room temperature ionic liquid electrolyte is selected from the group consisting of pyrrolidinium, 1-ethyl-3-methyl-imidazolium, bis(trifluoromethanesulfonyl)imide, and bis(fluorosulfonyl)imide. [Appendix 3] 2. The device of claim 1, wherein the salt of the ionic liquid electrolyte comprises lithium bis(fluorosulfonyl)imide salt (LiFSI). [Appendix 4] 4. The device of any one of claims 1 to 3, wherein the ionic liquid electrolyte comprises PYR13FSI. [Appendix 5] 5. The apparatus of any one of claims 1 to 4, wherein the anode comprises a bulk type composite anode. [Appendix 6] 6. The apparatus of claim 5, wherein the bulk composite anode has a thickness greater than about 5 micrometers. [Appendix 7] A process for charging and discharging a battery, the battery comprising: an anode comprising an active material, the active material comprising nanosilicon particles, the nanosilicon particles being coated with cyclized polyacrylonitrile; an ionic liquid electrolyte comprising a room temperature ionic liquid electrolyte and a salt; a cathode; forming a solid electrolyte intermediate film containing fluorine, oxygen, sulfur, carbon, and lithium on all exposed surfaces of the anode; The method includes:

Claims

1. 1. An electrode system comprising: an active material including a plurality of nanosilicon; a polyacrylonitrile polymer that binds the active material to conduct electricity and lithium ions, the polyacrylonitrile polymer conformally and individually covering each of the plurality of nanosilicon particles. An electrode system; A second electrode; and a room temperature ionic liquid electrolyte for contacting the electrode system with a second electrode, the room temperature ionic liquid electrolyte comprising a cationic species selected from the group consisting of pyrrolidinium and 1-ethyl-1-3-methylimidazolium; 1. An electrical energy storage device comprising:

2. The device of claim 1 , wherein the electrode system comprises a nanocomposite of cyclized polyacrylonitrile silicon (nSi-cPAN).

3. The electrode system comprises nSi-cPAN and the room temperature ionic liquid electrolyte is PYR 13 The apparatus of claim 1 comprising a FSI.

4. The device of claim 3 , wherein the electrode system comprises a bulk type composite electrode.

5. The apparatus of claim 4 , wherein the bulk electrode has a thickness greater than about 5 micrometers.

6. The device of claim 1 , wherein the nanosilicon particles have a size in the range of 1 to 500 nm.

7. 10. The device of claim 1, wherein the electrode system comprises about 70 wt% nanosilicon particles and about 30 wt% polyacrylonitrile polymer.

8. The device of claim 1 , wherein the electrode system has a thickness in the range of 10 to 50 μm.

Citation Information

Patent Citations

  • Lithium secondary battery using ionic liquid

    JP2010097922A

  • Nonaqueous electrolytic solution containing ionic fluid, and lithium secondary battery

    JP2013089365A

  • Method for making sulfurized polyacrylonitrile

    US20120059129A1

  • Composite Anode Of Lithium-ion Batteries

    US20140186701A1

  • Lithium secondary battery

    WO2009011249A1